Does Holding a Postdoctoral Position Bring Benefits for Advancing to Academia? - Eric S. Lin; Shih-Yung Chiu (Institute for the Study of Labor (IZA), 2015)
Postdoc is a special transitional position for those with a doctoral degree and is usually regarded as an investment to accumulate the additional human and social capital needed to facilitate future job searches or to add to an academic reserve army of unemployed PhDs. Given the prevalence of postdoctoral positions nowadays, it is crucial to explore the role played by postdoctoral participation in the post-PhD labor market. By taking advantage of a comprehensive data set from the National Profiles of Human Resources in Science and Technology in Taiwan, we first explore several characteristics associated with the choice of a postdoctoral position for newly-minted doctoral degree holders, such as age, discipline or the time taken to complete the degree. We then apply the control function approach to address the possible endogenous decision of postdoctoral experience when estimating the effects of postdoctoral positions on the current career choices between academic and non-academic jobs. The empirical results suggest that engaging in postdoctoral positions could increase the probability of advancing to the academic sector by about 6.1%. The heterogeneous effects of gender, major and cohort in regard to the postdoctoral experience are also found by splitting the data. Moreover, we experiment with several groupings for the definition of being awarded an academic position and obtain very robust empirical results.
Keywords: I2; J24; 330; academia; postdoctoral position; PhD; job choice